Cittaraga: Healing Dance Studio Based On Traditional Sundanese Dance - Herdiani, Een; Munggaran, Muhammad Mughni (Pascasarjana ISBI Bandung, 2023)
Having a healthy body is the hope of every human being because with excellent health life feels more meaningful. To maintain a healthy body, routine and regular activities are needed through medical health checks and other activities such as sports and dancing. Dancing for health has not been revealed by many researchers. Generally, people understand functions for ritual, entertainment, and performance needs. However, there is a function of dance for health that has not been discussed much. This study aims to reveal one of the studio activities that develop dance for health, namely Studio Cittaraga in Bandung. This studio develops healing dance using traditional Sundanese dance movements. Qualitative-descriptive methods are used to uncover these problems. The objects he studied were the perpetrators, both figures of healing dance developers at the Cittaraga studio and training participants. Observation, interviews, and documentation carry out data collection techniques. The results showed that Studio Cittaraga succeeded in developing traditional Sundanese dance movements for healing needs carried out continuously and enjoyably.